KAJIAN IDENTIFIKASI POTENSI DAN PERMASALAHAN SUMBERDAYA AIR: Studi Kasus : Kabupaten Belitung - HARIYANTO, ASEP; ISKANDAR, K. HERRY (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2011)
This study aims to provide an overview of potential and problems of water resources contained in Belitung District, as well as inputs for the Government Belitung Regency in order management and utilization of water resources. The method used is the primary method of survey and secondary survey methods. Primary survey methods include: surveys of ground water, spring surveys, and surveys of surface water. While the method of secondary survey conducted through secondary data collection and is a confirmation of the results of previous studies or Based on the information from the agencies related to water resource management. The method of analysis used in this study is